Dexmedetomidine enhances tolerance to bupivacaine cardiotoxicity in the isolated rat hearts: alpha 2 adrenoceptors were not involved - Fangfang Xia; Zhousheng Jin; Tingting Lin; Xixi Cai; Linmin Pan; Shi Wang; Yaoyao Cai; Hongfei Chen (BMC, 2019)
Abstract Background Dexmedetomidine was proved to mitigate bupivacaine-induced cardiotoxicity but mechanism of this ability is still unclear. This study was designed to investigate the direct effects of dexmedetomidine on cardiotoxicity induced by bupivacaine on Langendorff rat heart preparation and the role of alpha 2 adrenoceptors in this process was explored. Methods Hearts of rat were isolated, mounted on a Langendorff system. Five experimental groups were assessed after 10 min Krebs-Henseleit buffer (KHB) infusions as follow: (1) Group Con, only KHB was perfused; (2) Group Dex, KHB was perfused for 5 min, then dexmedetomidine (10 nmol/L) was added; (3) Group Bupi, KHB was perfused for 25 min, then bupivacaine (50 μmol/L) was added; (4) Group Bupi + Dex, KHB was perfused for 5 min, then the dexmedetomidine (10 nmol/L) was added for 20 min, at last a mixture of KHB + dexmedetomidine + bupivacaine were perfused; (5) Group Bupi + Dex + Yoh, a combination of KHB + yohimbine (alpha 2 adrenoceptor antagonists, 1 μmol/L) was perfusion for 5 min, then dexmedetomidine (10 nmol/L) was added for 20 min, at last a mixture of KHB + yohimbine + dexmedetomidine + bupivacaine was perfused. The experimental perfusion was maintained for 35 min in group Con and group Dex, and the experimental perfusion was sustained until asystole in the other three groups. Results Compared with group Bupi, dexmedetomidine significantly increased the time to first arrhythmia (P <  0.001) and time to asystole (P <  0.001) in group Bupi + Dex. In addition, dexmedetomidine also significantly increased the time to 25, 50 and 75% reductions in heart rate (P <  0.001) and the time to 25, 50 and 75% reductions in rate-pressure product (P <  0.001) in group Bupi + Dex. Dexmedetomidine increased the cardiac tissue bupivacaine content when asystole (Bupi + Dex vs. Bupi, 58.5 ± 6.3 vs. 46.8 ± 5.6 nmol/g, P = 0.003). The benefit of dexmedetomidine on bupivacaine-induced cardiotoxicity were not eliminated by yohimbine. Conclusions Dexmedetomidine could delay the occurrence of bupivacaine-induced arrhythmia and asystole in the isolated rat hearts, but the alpha 2 adrenoceptors were not involved in this process.